2006
DOI: 10.1300/j045v22n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Immunization Coverage in US States

Abstract: Although research suggests numerous interventions that can improve immunization coverage (Taskforce on Community Preventive Services, 2000), there is often a gap between policies supported by and public entities. The question for this study is whether the variation in childhood (19 to 35 months) immunization coverage rates across states is related to significant variations in state regulatory regimes that may optimize the benefits of state registries and systems that are designed to improve assessment of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Changing ImmTrac2 to opt-out has two primary benefits including increased vaccination coverage and cost savings. Opt-out registries are associated with increased statewide vaccine coverage compared to states with opt-in registries such as ImmTrac2 [16]. Additionally, Bloom et al found that changing ImmTrac2 to opt-out may be more cost-effective than current opt-in consent processes allowing limited resources to be allocated elsewhere [17].…”
Section: Discussionmentioning
confidence: 99%
“…Changing ImmTrac2 to opt-out has two primary benefits including increased vaccination coverage and cost savings. Opt-out registries are associated with increased statewide vaccine coverage compared to states with opt-in registries such as ImmTrac2 [16]. Additionally, Bloom et al found that changing ImmTrac2 to opt-out may be more cost-effective than current opt-in consent processes allowing limited resources to be allocated elsewhere [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HPV vaccination prevalence in the cervical PROSPR I cohorts may not reflect true prevalence since immunizations received outside of the health care systems may be less complete for new enrollees, those with limited utilization history, or in states (e.g., Texas) with opt-in immunization registries. 38,39 Published age-specific hysterectomy prevalence estimates are not available for New Mexico and this is a limitation of the results presented in the supplemental table. Additionally, hysterectomy prevalence as ascertained by EHR documentation of an absent cervix in the KPWA, KPNC, and KPSC cohorts appears to be lower than some national survey estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that switching from opt in to opt out could save more than $1 million per year in 1 state, 22 and at least 1 study has suggested that opt out policies may correlate with improved immunization coverage. 23 …”
Section: Discussionmentioning
confidence: 99%